UPAYA MENINGKATKAN KINERJA GURU MELALUI SUPERVISI DI SD NEGERI 013 SUKA MAJU KECAMATAN KUANTAN SINGINGI - Rokmawirda Rokmawirda (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is a school follow-up study which is motivated by the low performance of teachers of Public Elementary School013 Suka Maju for the effort to improve teacher performance by applying supervision. This research was conducted in PublicElementary School 013 Suka Maju, with research subjects being teachers of Public Elementary School 013 Suka Maju with atotal of 18 teachers. The data used in this study is data about teacher performance. This study was conducted in two cycles,with four stages: planning, implementation, observation and reflection. The results showed that in the first cycle the averagepercentage of achievement was 57.40% or with a fairly good category. In the learning planning indicator the teacher'sability is 61.11, on the understanding of the teacher's ability of 55.55, and in the development of the teacher's curriculum orsyllabus of 55.55 and in the second cycle the average percentage of achievement is 77.78 or with good category. on thelearning planning indicator the ability of the teacher is 77.78, on the understanding of students the ability of the teacher is83.33, and in the development of the curriculum or syllabus the teacher's ability is 72.22. Based on this acquisition, it can beconcluded that the performance of teachers of Public Elementary School 013 Suka Maju has increased after supervision wasapplied.